2012
DOI: 10.5963/lsmr0201002
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Estimation of Bioactive Compound Present in Centella Asiatica: An Important Medicinal Plant

Abstract: Abstract-Qualitative phytochemical analysis of this plant confirms the presence of various phytochemicals like alkaloids, flavonoids, tannins, terpenoids, saponin, steroids, and proteins, reducing sugars, carbohydrates and cardiac glycosides in its methanolic extracts. This paper deals with the significance of these phytochemicals with respect to the role of these plants in traditional medicinal system. This preliminary study draws attention to the need for further studies of the active principles identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Similarly, standard phytochemical screening was performed for the detection of flavonyl glycosides, lipids and flavanoids (Singh et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, standard phytochemical screening was performed for the detection of flavonyl glycosides, lipids and flavanoids (Singh et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…) was used for the detection of steroids; sulphuric acid test (Firdouse and Alam ) was used for the detection of quinines; ferric chloride test (Firdouse and Alam ) was used for the detection of phenols; biuret, ninhydrin and Bradford assays (Singh et al . ) were used for the detection of proteins. Similarly, standard phytochemical screening was performed for the detection of flavonyl glycosides, lipids and flavanoids (Singh et al .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have showed that biological activities of phytochemicals are comparable to previous synthetic compounds, and they have very low side effects. The most important bioactive constituents of plants include alkaloids, tannins, steroids, terpenoids, flavonoids, and phenolic compounds (Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Crude extracts of cassava and fern leaves were prepared by boiling method (Bakhtiar et al, 1994) and those of pegagan, fruit pericarp of mangosteen and stem bark of A. scholaris by macerated with methanol (Singh et al, 2012;Orozco and Failla, 2013).…”
Section: Preparing Crude Extractmentioning
confidence: 99%
“…Groups of secondary metabolites potentially developed as biostimulants are mostly found in tropical plants like in leaves of cassava (Manihot esculenta) and fern (Gleichenia linearis) containing flavonoid (Bakhtiar et al, 1994), fruit pericarp of mangosteen (Garcinia mangostana) containing xanton (phenolic) (Orozco and Failla, 2013), stem bark of Alstonia scholaris containing alkaloid (Marliana and Ismail, 2011), and Centella asiatica containing terpenoid (Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%